Dietary caffeine and brain dopaminergic function in Parkinson's disease - Saarinen, Emmi (My University, 2025)
Objective: To investigate the effects of dietary caffeine intake on striatal dopamine function and clinical symptoms in Parkinson’s disease in a cross-sectional and longitudinal setting. Methods: 163 early Parkinson’s diseases patients and 40 healthy controls were investigated with [123I]FP-CIT single photon emission computed tomography, and striatal dopamine transporter binding was evaluated in association with the level of daily coffee consumption and clinical measures. After a median interval of 6.1 years, 44 patients with various caffeine consumption levels underwent clinical and imaging re-examination including blood caffeine metabolite profiling. Results: Unmedicated early Parkinson’s disease patients with high coffee consumption had 8.3-15.4% lower dopamine transporter binding in all studied striatal regions than low consumers, after accounting for age, sex and motor symptom severity. Higher caffeine consumption was further associated with a progressive decline in striatal binding over time. No significant effects of caffeine on motor function were observed. Blood analyses demonstrated a positive correlation between caffeine metabolites after recent caffeine intake and dopamine transporter binding in the ipsilateral putamen. Interpretation: Chronic caffeine intake prompts compensatory and cumulative dopamine transporter downregulation, consistent with caffeine’s reported risk reduction in Parkinson’s disease. However, this decline does not manifest in symptom changes. Transiently increased dopamine transporter binding after recent caffeine intake has implications for dopaminergic imaging guidelines.